Javanese Gamelan Art in Malay Community in Tanjung Balai City (Muliticultural study) - Maya Ningsih Lubis; Sunarto Sunarto; Syahrul Syah Sinaga; Rahina Nugrahani (International Conference on Science, Education, and Technology, 2023)
The Malay community in the city of Tanjungbalai can accept Javanese gamelan music as well as the Javanese. The role of the Malay community in Javanese gamelan music performances is not only as spectators but the Malay community also learns and participates in playing Javanese gamelan instruments in the Langen Hidayah Jati Group. Javanese Gamelan Art in the Malay Community can be seen when the presentation of the campursari music which is performed during the people's party is the Malay song iyolah comely accompanied by Javanese gamelan music. This study aims to examine the phenomenon of the existence of Javanese gamelan arts in the Malay community in the city of Tanjungbalai in multicultural studies. The research location is Tanjungbalai City, North Sumatra Province. Data collection techniques are observation, interviews, and document studies. The data validity technique uses source triangulation. Data analysis technique using descriptive analysis. The result of this research is that the Multicultural Study is grouped into three models, namely: the Introduction Model, the Practice Model and the Transformation Model. Multicultural understanding will create harmony in a society that understands, respects and respects art from other cultures, especially Javanese art that is in the Malay community in the city of Tanjung Balai.